Wpływ charakterystyki komunalnych osadów ściekowych na efekty kofermentacji z serwatką = Effect of municipal sewage sludge in results of co-digestion with whey - Zielewicz, Ewa; Tytła, Malwina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the methods of disposal of acid wheymay be the fermentation of municipal sewage sludge. Dosage whey waste water should not interfere with the fermentation process, and also deteriorate the susceptibility of fermented sludge dewatering. Co-digestion effects obtained for the same proportion of whey in 2 municipal sludge have shown that an important role in determining the doses of whey can play ratio of COD whey / COD sludge.
Keywords: kofermentacja; fermentacja metanowa; osady ściekowe; serwatkakwaśna; biogaz; co-digestion; digestion; sludge; acid whey; biogas